Effect of methionine:lysine ratio on growth performance and blood metabolites of growing-finishing pigs - Kats, L.J.; Friesen, K.G.; Richert, B.T.; Owen, K.Q.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty growing-finishing pigs (40 barrows and 40 gilts) were used in three consecutive growth assays to determine the optimum methionine:lysine ratio for pigs weighing from 48 to 107 lb, 120 to 179 lb, and 191 to 245 lb, respectively. Each growth assay was to be conducted for a 28-d period with a 14-d transition period between assays. Pigs were allotted by weight and placed in pens each containing one barrow and one gilt. Pigs were assigned to one of eight experimental treatments with five replicate pens per treatment. Pigs were fed diets containing either high lysine (1.0, .9, or .8%, respectively) or low lysine (.8, .7, or .6%, respectively) with dietary methionine at 24.5, 28, 31.5, or 35% of lysine. This would correspond to total sulfur-containing amino acids (methionine + cystine) of 49, 56, 63, and 70% relative to lysine. During the first study (48 to 107 lb), average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) improved with increasing dietary lysine. Although no differences occurred in growth performance with increasing methionine ratio, there was a numeric improvement in growth performance for those pigs receiving diets containing 28% methionine relative to lysine. A lysine × methionine interaction was observed for blood urea N with pigs having the lowest BUN values observed with methionine at 24.5 and 31.5% of lysine for pigs fed .8 and 1.0% lysine, respectively. During phase II (120 lb to 179 lb), ADG improved with increasing dietary lysine and showed a linear response to increasing methionine ratio. Feed efficiency was also improved with increasing dietary lysine. For the third phase (191 to 245 lb), ADG also improved with increasing dietary lysine. There were no significant differences in feed intake; however, feed efficiency improved with increasing dietary lysine. In summary, because of high ADFI observed in these studies, the dietary methionine levels used closely met or exceeded the pig's requirement on a grams/day basis. Therefore, these data suggest that increasing dietary methionine does not improve pig performance.
Keywords: Swine; Lysine; Methionine; Growth performance; Growing-finishing